Dance Movements Enhance Song Learning in Deaf Children with Cochlear Implants - Vongpaisal, Tara; Caruso, Daniela; Yuan, Zhicheng (Frontiers in Psychology, 2016)
Music perception of cochlear implants (CI) users is constrained by the absence of salient musical pitch cues crucial for melody identification, but is made possible by timing cues that are largely preserved by current devices. While timing cues are a potential route to music learning, it is not known to what extent these timing cues are perceptible to CI users in complex sound scenes, especially when pitch and timbral features can co-occur and obscure temporal features of music. The task at hand, then, becomes one of optimizing the available timing cues for young CI users by exploring ways that they might be perceived and encoded simultaneously across multiple modalities. Accordingly, we examined whether training tasks that engage active music listening through dance might enhance the song identification skills of deaf children with CIs. Nine CI children learned new songs in two training conditions: a) listening only (auditory learning), and 2) listening and dancing (auditory-motor learning). We examined children’s ability to identify original song excerpts, as well as mistuned, and piano melodic versions from a closed-set task. While CI children were less accurate than their normal peers, they showed greater song identification accuracies in versions that preserved the original instrumental beats following learning that engaged active listening with dance. The observed performance advantage is further qualified by a medium effect size, indicating that the gains afforded by auditory-motor learning are practically meaningful. Furthermore, kinematic analyses of body movements showed that CI children synchronized to temporal structures in music in a manner that was comparable to normal hearing age-matched peers. Our findings are the first to indicate that input from CI devices enables good auditory-motor integration of timing cues in child CI users for the purposes of listening and dancing to music. Beyond the heightened arousal from active engagement with music, our findings indicate that a more robust representation or memory of musical timing features was made possible by multimodal processing. Methods that encourage CI children to entrain, or track musical timing with body movements, may be particularly effective in consolidating musical knowledge than methods that engage listening only.